Bird diversity in pine-oak forests from central Guerrero, Mexico - Almazán-Núñez, R. Carlos; Puebla-Olivares, Fernando; Almazán-Juárez, Ángel (Instituto de Ecología, A.C., 2009)
We assessed bird species richness and their abundances at three sites with pine-oak forest under different development stages (mature forest, regenerating forest and shade coffee plantation) in central Guerrero, Mexico. We recorded a total of 117 species and 1,276 individuals; however, analysis of cumulative species curves indicates that it is possible to find more species in the region for a more complete list. There were significant differences in species diversity among the three sites. Species diversity was higher at the regenerating forest, middle in mature forest and lowest at shade coffee plantation. Higher similarity was between mature forest and regenerating forest. There were no significant differences among the feeding guilds at any site. The mid-stratum had the highest utilization at the three sites. In addition, there were significant differences among strata in regenerating forest in comparison with mature forest and shade coffee plantation.